Failures to Punish: Command Responsibility in Domestic and International Law - Sepinwall, Amy J (2009)
This Article embraces one of two contested understandings of what a failure to punish entails. On the first understanding, a military commander's failure to punish is construed solely as a dereliction of duty. Accordingly, his failure to punish constitutes a separate offense from the underlying atrocity that his troops have committed. The failure to punish is, then, a substantive offense in its own right. On a second understanding, for which I argue here, the failure to punish renders the commander criminally liable for the atrocity itself, even if he neither ordered nor even knew about the atrocity before its occurrence. Here, then, the failure to punish is a mode of liability-it grounds an ascription of the atrocity of one's soldiers to their commander, but does not capture an offense in its own right. For the sake of brevity, I shall refer to these two understandings, respectively, as the substantive offense view and mode of liability view, and I shall follow international and domestic law in employing the term failure to punish as a catch-all for the failure to undertake the duty with which commanders are charged to investigate, report, refer, discipline, punish, and so on